Enhancement of radiation tolerance in GaAs/AlGaAs core–shell and InP nanowires. (4th April 2018) - Li, Fajun; Xie, Xiaolong; Gao, Qian; Tan, Liying; Zhou, Yanping; Yang, Qingbo; Ma, Jing; Fu, Lan; Tan, Hark Hoe; Jagadish, Chennupati
Abstract: Radiation effects on semiconductor nanowires (NWs) have attracted the attention of the research community due to their potential applications in space and atomic fields. The effective implementation of NW devices in a radiation environment is a matter of concern. Here, the photoluminescence (PL) and time-resolved PL (TRPL) measurements were performed on both GaAs and InP NWs at room temperature before and after 1 MeV H + irradiation with fluences ranging from 1 × 10 11 to 5 × 10 13 p cm −2 . It is found that the degradation of lifetime is size-dependent, and typically the minority carrier lifetime damage coefficient is closely correlated with the material and NW diameter. Compared to GaAs and InP bulk material counterparts, the lifetime damage coefficient of NWs decreases by a factor of about one order of magnitude. After irradiation, GaAs NWs with a smaller diameter show a much lower lifetime damage coefficient while InP NWs show an increase in carrier radiative lifetime. The increased size-dependent radiation hardness is mainly attributed to the defect sink effect and/or the improvement of a room temperature dynamic annealing mechanism of the NWs. The InP NWs also showed higher radiation tolerance than GaAs NWs.